MANUSCRIPTS DO NOT BURN - Akhmedova Shokhista (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the manuscript of the literary script “Ibn Sina Bukharoda”, which has not been published so far from the personal archive of the poet Omon Matjan, and its artistic features were analyzed.